2021
DOI: 10.4149/neo_2021_201110n1198
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TUG1 promotes Ewing's sarcoma cell proliferation, migration, and invasion via the miR-199a-3p-MSI2 signaling pathway

Abstract: The aim of this study was to investigate the roles and potential mechanisms of long non-coding RNA (lncRNA) taurine upregulated gene 1 (TUG1) in the proliferation, migration, and invasion of Ewing's sarcoma cells.RT-qPCR was used to detect the expression of TUG1,, and musashi2 (MSI2) in Ewing's sarcoma tissues and cell lines. Kaplan-Meier overall survival curves showed the survival rates of Ewing's sarcoma patients with high and low exp ression of TUG1. The association between the expressions of TUG1/MSI2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The large number of lncRNAs produced by human cells contributes an important role to various biological processes, including genome expression and cell differentiation [ 25 ]. Recent studies suggest that an abnormal expression of lncRNA may play a role in the progression and development of cancer [ 26 , 27 ]. However, there is currently little research investigating cuproptosis-associated lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of lncRNAs produced by human cells contributes an important role to various biological processes, including genome expression and cell differentiation [ 25 ]. Recent studies suggest that an abnormal expression of lncRNA may play a role in the progression and development of cancer [ 26 , 27 ]. However, there is currently little research investigating cuproptosis-associated lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In Ewing’s sarcoma tissues and cells, the down-regulation of lncRNA TUG1 (taurine up-regulated gene 1) or overexpression of miR-199a-3p could inhibit cell proliferation, migration, and invasion. TUG1, as a ceRNA, regulated the expression of MSI2 (musashi2) by sponging miR-199a-3p, thereby promoting the malignant phenotype of Ewing’s sarcoma cells [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, the role of lncRNAs is creating emerging concern in biological processes such as cells proliferation and differentiation 29 . Recent studies have found that dysregulation of lncRNAs may lead to tumorigenesis and progression 30,31 . However, little research was conducted on lncRNA associated with cuproptosis.…”
Section: Discussionmentioning
confidence: 99%